Central European Innovative Practices Supporting Active Ageing - Bihari, Ildikó; Czibere, Ibolya; Csoba, Judit; Kerekes, Noémi; Rácz, Andrea (METSZETEK Társadalomtudományi Folyóirat, 2022)
The study presents through international examples of how the security and quality of life of elderly and disabled people can be enhanced. 12 partners in eight Central European countries carried out pilot activities within the framework of the HELPS project. The aim of this international project is to contribute to the decrease of the social exclusion of elderly, and to elaborate practises through which seniors would not be constraint to institutional care, and can live in their homes on a longer term. The study presents the outcomes of these pilots and the ensuing primary experiences. The presented innovative solutions offer possibilities in various fields (housing, services, career, practises, information of relatives) for the home care of elderly and people living with disabilities. Prior to the elaboration and put into practice of the development ideas and plans, the partners evaluated the health care system and related services offered to elderly and disabled people in their homeland. The analyses revealed those shortage areas, where further developments would increase the possibility to keep and care for the target group in their homes.